Religious affections how man's will affects his character before God - Edwards, Jonathan 1703-1758; Houston, James Macintosh, 1922- (Portland, OR Multnomah, 1984)
Includes bibliographical references and indexes.
Abridged edition of : Treatise concerning the religious affections. 1808
Keywords: Edwards, Jonathan, -- 1703-1758; Emotions -- religous aspects -- Christianity -- early works to 1800.